2001
DOI: 10.1002/gene.1064
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of heat shock transcription factor HSF1 in zebrafish causes heat‐induced apoptosis

Abstract: The heat shock transcription factor HSF1 regulates the stress-inducible expression of heat shock proteins (HSPs) and other molecular chaperones that are involved in higher order protein structure and assembly. HSPs protect organisms against environmental challenges. Targeted disruption of the murine Hsf1 gene results in massive heat-induced apoptosis in cells deficient in HSF1. To explore whether zebrafish HSF1 has overlapping function with mammalian HSF1, we inhibited zebrafish HSF1 expression during developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Expression of hsf1 was found to increase only in gills of seawater-and hypersaline-adapted sea bream, an effect that followed the same profile as hsp70. It is likely that transcription of hsp70 is regulated via hsf1, since recent studies using fish and mammalian models have provided conclusive evidence for a regulatory link between these two genes (42,55,60). An elevated hsf1 transcription would be a critical determining factor for maintaining sufficient hsp70, and as such the combined upregulation of both of these genes could be one reason as to why gills of euryhaline fish have the capability to maintain cellular functions, even under severe stress such as hypersaline exposure.…”
Section: Discussionmentioning
confidence: 96%
“…Expression of hsf1 was found to increase only in gills of seawater-and hypersaline-adapted sea bream, an effect that followed the same profile as hsp70. It is likely that transcription of hsp70 is regulated via hsf1, since recent studies using fish and mammalian models have provided conclusive evidence for a regulatory link between these two genes (42,55,60). An elevated hsf1 transcription would be a critical determining factor for maintaining sufficient hsp70, and as such the combined upregulation of both of these genes could be one reason as to why gills of euryhaline fish have the capability to maintain cellular functions, even under severe stress such as hypersaline exposure.…”
Section: Discussionmentioning
confidence: 96%
“…Although these features are also readily recapitulated in other model systems, zebrafish embryos offer certain advantages for modeling polyQ disease: they develop rapidly and externally, can be produced quickly in large numbers, and are transparent, permitting direct analysis of organs, tissues, and fluorescently tagged proteins. In addition, pathways and components of protein QC have been identified that are conserved from zebrafish to humans, including an HSF1-dependent stress response and a zebrafish ortholog of human CHIP (Wang et al, 2001;Strausberg et al, 2002). Antisense morpholinos can efficiently knock down expression of zebrafish genes, raising the possibility of studying candidate suppressor and enhancer genes (Nasevicius and Ekker, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-sense morpholino oligonucleotides were dissolved in 1ϫ Danieau's buffer in a stock concentration of 20 ng/nl (Nasevicius and Ekker, 2000). For morpholino microinjection, one-to two-cellstage zebrafish embryos were injected with either Brg1-MO or control-MO (5Ј-CCTCTTACCTCAGTTACAATTT-ATA-3Ј) (5 or 10 ng) (Wang et al, 2001). At different stages post-morpholino injections, embryos were fixed in 4% paraformaldehyde (PFA) and gene expression was assayed by in situ hybridization.…”
Section: Morpholino and Rna Injectionsmentioning
confidence: 99%